Masterplan Pengembangan Desa Wisata Gerbosari Kecamatan Samigaluh Kabupaten Kulon Progo - Latri Wihastuti; Rina Oktavia (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2021)
Tourism development has become an option in many areas as a way to reduce poverty. One of the resources developed as a source of income is natural and cultural resources which are exploited as tourist objects and attractions. Tourism can be developed to improve the economy that is directly towards the community around attractions. Gerbosari Village is one of the leading villages in Samigaluh Subdistrict, Kulonprogo Regency which has a special tourism potential for use by tourist villages. The potential given by Gerbosari Village is a chrysanthemum plant whose data grows well, ponders beautiful nature, and harmonious community culture. The Village Government and Gerbosari Residents have a strong commitment to managing the potential of the village and creating innovations to enhance development through local tourism development. To realize the developed tourist village and provide direction to the welfare needed by the Gerbosari Tourism Village development masterplan. Based on the results of the preparation of the Gerbosari Tourism Village Development Masterplan, several Tourism Village objects that will be developed in the next 5 years include chrysanthemum agro-tourism areas, educational tours for the use of home yards, Camping ground and tracking of Jongkang Mountain, and the peak Cultural Tourism of Suroloyo.